Acute cellular rejection treatment outcomes stratified by Banff grade in pediatric kidney transplant. (7th December 2018) - Chen, Justin; Liverman, Rochelle; Garro, Rouba; Jernigan, Stephanie; Travers, Curtis; Winterberg, Pamela D.
Abstract: Introduction: There are limited data to guide optimal treatment strategies for acute cellular rejection (ACR) based on Banff grade for pediatric kidney transplant recipients. This report reviews a large pediatric transplant center's experience with ACR. Materials and Methods: A retrospective analysis of pediatric kidney transplant recipients at our center from 2007 to 2014 was performed. Primary outcomes were incidence of graft failure and graft function one year following ACR based on Banff grade and treatment received. Results: A total of 204 patients were reviewed, of which 65 received rejection treatment with either an oral steroid cycle (n = 16), intravenous steroid pulse (n = 28), or anti‐thymocyte globulin (rATG, n = 21). Overall, patients received rATG for treatment of more severe rejection associated with impaired graft function and as a group experienced statistically significant improvements in eGFR over the year following treatment, though most did not regain baseline graft function. Discussion: Our data suggest that rATG is partially effective in treating ACR, but our study was underpowered to determine the effect of different treatments based on Banff grade. Since there is limited literature to guide clinical treatment of ACR in children, large transplant centers should collaborate to evaluate outcomes and establish evidence‐based practice.